An Architecture of Exception: Transgressing the Everyday – Superflex's Flooded McDonald's. (November 2013) - Mosley, Jonathan; Mosley, Jonathan; Sara, Rachel
Abstract In Flooded McDonald's, a film by Danish artists' collective Superflex, the familiar sight of the fast‐food restaurant is replaced by 'a slowly emerging apocalyptical composition', as the interior floods, objects are displaced and the retail space fills with water. Jonathan Mosley describes how this destabilised and other disaster‐invoked visions of architecture – structures and spaces breaking down – enable us to use our imagination to test the parameters of the everyday.